A decade (and a global financial crisis) after Blinder: The interaction between researchers and policy-makers in central banks - Matthieu Bussière; Livio Stracca (European Central Bank (ECB), 2010)
Periods of economic and financial stress traditionally give rise to profound changes in economic theory and in the way policy decisions are taken. Motivated by the recent interest in renewing macroeconomics after the global financial crisis, we collected the views of senior central bank staff in 32 central banks by means of a special questionnaire on a number of issues related to the interaction between research and policy-making. Thereafter, the paper first surveys the existing literature on the relation between researchers and practitioners and offers some reflections on the fundamental and practical differences between research and policy work. Finally, it delves on the issue of model-based versus judgment-based approaches to economic forecasts and policy simulations, with a special emphasis on the growing role of DSGE models within central banks. We conclude with practical suggestions on how best to integrate models and research into policy making decisions.
Keywords: A11; C1; D58; 330; central bank communication; DSGE Models; economic crises; Economic research; policy making; Wirtschaftsforschung; Zentralbank; Geldpolitik; Politische Entscheidung; Dynamisches Gleichgewicht; Wissenschaftliche Methode